Comorbidities in lung cancer: prevalence, severity and links with socioeconomic status and treatment. Issue 1064 (27th March 2014) - Grose, Derek; Morrison, David S; Devereux, Graham; Jones, Richard; Sharma, Dave; Selby, Colin; Docherty, Kirsty; McIntosh, David; Louden, Greig; Nicolson, Marianne; McMillan, Donald C; Milroy, Robert; et al.
Abstract: Background: Survival from lung cancer remains poor in Scotland, UK. Although the presence of comorbidities is known to influence outcomes, detailed quantification of comorbidities is not available in routinely collected audit or cancer registry data. The aim of the present study was to assess the prevalence and severity of comorbidities in patients with newly diagnosed lung cancer across four centres throughout Scotland using validated criteria. Methods: Between 2005 and 2008, all patients with newly diagnosed lung cancer coming through the multidisciplinary teams in four Scottish centres were included in the study. Patient demographics, WHO/Eastern Cooperative Oncology Group performance status, clinicopathological features and primary treatment modality were recorded. Results: Details of 882 patients were collected prospectively. The majority of patients (87.3%) had at least one comorbidity, the most common being weight loss (53%), chronic obstructive pulmonary disease (43%), renal impairment (28%) and ischaemic heart disease (27%). A composite score was produced that included both number and severity of comorbidities. One in seven patients (15.3%) had severe comorbidity scores. There were statistically significant variations in comorbidity scores between treatment centres and between non-small cell lung carcinoma treatment groups. Disease stage was not associated with comorbidity score. Conclusions: There is a high prevalence of multiple, severe comorbidities in Scottish patients with lung cancer, and these vary by site and treatment group. Further research is needed to determine the relationship between comorbidity scores and survival in these patients.